Investigating microvascular outcomes with ischemic preconditioning and passive stretch - Fenn, Sarah A.; Dobbs, Ward C.; Walker, Maxwell K.; Scheuermann, Britton C.; Caldwell, Jacob T. (Physiological reports, 2025)
This study examined the effects of intermittent passive stretching (PS) and ischemic preconditioning (IPC) on microvascular responsiveness and muscle oxidative capacity. We hypothesized that PS would lead to greater improvements in vascular function and oxidative capacity than IPC. Eighteen healthy male and female participants completed a randomized crossover design, undergoing post‐occlusive reactive hyperemia (PORH) and oxidative capacity testing. PS involved bilateral foot splinting to moderately stretch the gastrocnemius and soleus, while IPC used bilateral thigh cuff inflation. Each intervention consisted of four cycles of 5‐minute “on” and 5‐min “off” periods. A two‐way repeated measures ANOVA assessed condition by time interactions, and intraclass correlation coefficient evaluated the absolute agreement in resaturation rates. A significant main effect of time was observed for resaturation rates ( p < 0.01). Similarly, a main effect of time was found for the recovery rate constant, with increases observed in both the PS group [pre: 0.88 ± 0.23, post: 0.98 ± 0.28 min −1 ] and the IPC group [pre:0.90 ± 0.33, post: 0.97 ± 0.25 min −1 ] ( p = 0.019). These findings suggest that both methods, when used acutely, increase microvascular responsiveness and oxidative capacity. Given its ease of application, PS may serve as a practical tool for populations unable to engage in traditional exercise, offering a method to promote functional improvements.